Digital Financial Inclusion in Islamic Boarding Schools Practices, Challenges, and Socioeconomic Impacts on Indonesian Student - Umam, Khotibul; Sufiyanto, Mohammad Imam; Hefni, Mohammad; Faruq, Umarul; Luthfi, Moh. (Institut Agama Islam Negeri Madura, 2025)
This study analyzes digital financial inclusion practices in Islamic boarding schools, examining challenges and socioeconomic impacts on students. The research addresses the literature gap regarding digital financial service implementation in Islamic educational institutions and their effectiveness in promoting financial literacy among student communities. A qualitative approach was employed with two Islamic boarding schools: Pondok Pesantren Puncak Darussalam and Pondok Pesantren Al Amien Prenduen. Data collection involved comprehensive in-depth interviews, direct observations, and extensive documentation, analyzed through systematic data reduction and triangulation methods to ensure validity and reliability of findings. Digital financial inclusion significantly facilitates financial transactions, enhances student financial literacy, and reduces cash dependency among student. However, limited technological infrastructure and low parental financial literacy present substantial implementation challenges requiring attention. The positive socioeconomic impact manifests through improved student financial literacy, encouraging wiser financial management practices that can foster greater economic independence for future sustainability.